Suicide of Farmers and Farm Workers Amid COVID-19 in India - RH, Raghavendra; R, Anil Kumar; H, Shakunthala (Journal of Agricultural Extension Management, 2022)
The purpose of the study is to examine the current scenario of farmers’ suicide in India. Farmer suicides in India refer to the national catastrophe of farmers committing suicide since the 1990s. The farmers’ suicide rate in India had ranged between 1.4 and 1.8 per 100,000 total population, over a 10-year period through 2005, however the coronavirus disease (COVID-19) has impacted not only physical health but also mental health and wellbeing globally. These impacts can be critically higher among marginalized individuals and populations like farmers and agricultural laborers in India. While most of them live in poor socioeconomic conditions, recent psychosocial challenges due to the COVID-19 lockdown had brought endless suffering in their lives. In this way, present study depicts about farmers and farm workers suicide amind COVID 19 India has been discussed